Long-term effects of labor market conditions on family formation for Japanese youth - Yuki Hashimoto; Ayako Kondo (Osaka University, Institute of Social and Economic Research (ISER), 2010)
This study aims to examine how each cohort's family formation is affected by labor market conditions experienced in youth in Japan. Although deterioration in youth employment opportunities has often been blamed for Japan's declining marriage and fertility rates, the effects of slack labor market conditions on marriage and fertility are theoretically unclear. We estimate the effects of regional labor market conditions on marriage and fertility, controlling for nation-wide year effects and prefecture fixed effects, and find the following. First, the male unemployment rate is negatively correlated with marriage of women in the local labor market, although the correlation is weak and concentrated on the less educated group. Second, high school-educated women who experienced a recession while entering the labor market are less likely to have children and tend to marry later. In contrast, a recession at entry to the labor market rather increases fertility among college-educated women. The overall impact of labor market conditions experienced in youth on family formation is relatively weak, compared to the substantial losses in earnings and employment stability documented by the existing studies.
Keywords: 330; Arbeitsmarkt; Fertilität; Familienplanung; Junge Arbeitskräfte; Japan